Teacher’s attitudes towards and practice in cognitive reading strategies instruction - Bùi, Thị Vân Anh (University of Languages and International Studies, 2017)
The study was conducted to investigate high school teacher’s attitudes towards and practices in instructing cognitive reading strategies for mainstream students. It specifically explored teachers’ beliefs about the importance of cognitive reading strategies...